Local Conditions for Anti-immigrant Violence: A Qualitative Comparative Analysis (QCA) of Asylum Housing Attacks in Sweden - Törnberg, Anton (Terrorism and political violence, 2023)
This study uses a novel approach to identifying local contextual conditions conducive, alone or in combination to far-right political violence. The studied case is asylum housing attacks occurring in Sweden 2015–16. Using a fuzzy-set qualitative comparative analysis of eighty-six Swedish municipalities, forty-two of which have experienced arson attacks against refugee housing facilities, we operationalize and test four hypotheses derived from the literature. These assumed the causal impact of (1) objective grievances, (2) mediated grievances combined with lack of political opportunities, (3) independent alternative media effects, and (4) broader far-right mobilization. In contrast to a number of previous studies, none of the three first hypotheses received support. No operationalization of objective grievances, such as influxes of immigrants, poverty, or unemployment distinguished the municipalities where attacks had occurred. Nor did the local level of discursive or political opportunities. Only one of our expected causal pathways—arson attacks as an extension of a broader local far-right mobilization in the context of a supportive local public opinion—was a sufficient condition for a large proportion of our positive cases.